Enhancing Third-Grade Students’ Speaking Skills through the Integration of the Synectic Learning Model and the Extemporaneous Method - Linda Amelia Putri; Panca Dewi Purwati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: Based on initial observations conducted in the classroom, it appears that students' speaking skills are still low. They are not yet able to express ideas verbally, and the use of one-way learning models and approaches is the main cause. Given these issues, it is necessary to apply a synectic learning model with a deep learning approach assisted by extemporaneous methods. This study aims to describe, measure differences, and measure improvements in Indonesian speaking skills in third-grade elementary school students. The approach used is a mixed method (quantitative and qualitative). Qualitative data were obtained from observations, interviews, and documentation. Qualitative data explains the stages of activities and changes in student skills after the application of the synectic model, deep learning approach, and extemporaneous method. Quantitative data were obtained from the results of pretest and posttest speaking skills at SDN 02 Leteh with a total of 26 students. This study applies the second strategy synectic learning model, using analogies and speaking activities using a text framework to express understanding. The results of the Paired T-Test for the pretest and posttest proved that there was a significant difference between the two, with a t-value of -15.958 and a significance of 0.000. In addition, the N-Gain test results also showed a score of 0.6095 or 60%, indicating that the learning process provided was effective enough to improve students' speaking skills. The qualitative results reinforce the quantitative results, as demonstrated by the students' increased courage, fluency, and activity in speaking. Abstrak: Berdasarkan observasi awal yang dilakukan di kelas, memperlihatkan bahwa keterampilan berbicara siswa masih rendah. Mereka belum mampu mengungkapkan gagasan secara lisan, penggunaan pembelajaran yang satu arah menjadi penyebab utama utama. Melalui permasalahan tersebut, maka perlu adanya penerapan model pembelajaran sinektik dengan pendekatan deep learning berbantuan metode ekstemporer. Penelitian ini bertujuan untuk mendeskripsikan, mengukur perbedaan, serta mengukur peningkatan keterampilan berbicara bahasa Indonesia pada siswa kelas 3 sekolah dasar. Pendekatan yang digunakan adalah mixed method (kuantitatif dan kualitatif). Data kualitatif didapatkan dari hasil observasi, wawancara, dan dokumentasi. Data kuantitatif diperoleh dari hasil pretest dan posttest keterampilan berbicara di SDN 02 Leteh dengan jumlah 26 siswa. Penelitian ini menerapkan model pembelajaran sinektik strategi dua, menggunakan analogi dan kegiatan berbicara menggunakan kerangka teks untuk mengemukakan pemahamannya. Hasil Paired T-Test pretest dan posttest membuktikan adanya perbedaan signifikan antara keduanya, dengan nilai t-hitung -15,958 dan signifikansi 0,000. Selain itu, hasil uji N-Gain juga menunjukkan skor 0,6095 atau 60% yang menandakan bahwa perlakuan yang diberikan cukup efektif untuk meningkatkan keterampilan siswa dalam berbicara. Hasil kualitatif tersebut memperkuat hasil kuantitatif, sebagaimana terlihat dari meningkatnya keberanian, kelancaran, dan keaktifan para siswa dalam berbicara.